Trophic transfer of arsenic in the food chain from selected crops grown in long-term wastewater contaminated soil - Mudasra Munir; Kafeel Ahmad; Zafar Iqbal Khan; Shahzad Akhtar; Muhammad Nadeem; Asma Ashfaq; Mohammad Faisal; Abdulrahman A. Alatar; Hafiza Mamona Nazir; Ifra Saleem Malik (Agricultural Water Management)
Arsenic (As) contamination is a major health problem that exists worldwide. The accumulation of toxic metals in the surrounding soils of advanced industrial and agricultural sectors has the potential to degrade the ecosystem. All the soil and vegetable samples contaminated with different water sources were collected from three districts, namely, Jhang, Faisalabad and Toba Tek Singh. All samples were digested via the wet digestion method. Water, soil, vegetable, and human blood samples were analyzed to determine the concentration of arsenic via an atomic absorption spectrophotometer. The As content was greater in the soil (0.53–22.311 mg/kg) and vegetable (0.291–1.796 mg/kg) samples collected from Site 3, which were treated with wastewater. The As concentration ranged from 0.02444 to 2.287 mg/L in the blood serum. The potential health risks were evaluated by applying various indices, such as the accumulation factor, single pollution index, enrichment factor, estimated daily intake and target hazard quotient of arsenic. C esculenta presented the highest values for the accumulation factor (0.756) and enrichment factor (3.134). The study revealed a target hazard quotient (THQ) exceeding 2 at several sites, posing potential health risks. Leafy vegetables irrigated with wastewater accumulated arsenic above permissible limits due to soil contamination. However, arsenic contamination can have a direct impact on soil, metal uptake by vegetables and human health. The study highlights that human activities have intensified metal pollution in the area, necessitating immediate cessation of such practices. Environmentally friendly wastewater management methods should be implemented, and regular monitoring of toxic metals in water, soil, and vegetables is crucial to prevent excessive arsenic accumulation.